2013
DOI: 10.3354/meps10246
|View full text |Cite
|
Sign up to set email alerts
|

Predicting fish recruitment from juvenile abundance and environmental indices

Abstract: Prediction of year-class strength is a critical challenge for fisheries managers. Theoretically, predictions of recruitment should be better when they are based on estimates of cohort size taken close to the age of recruitment and may improve if the effects of environmental factors that influence pre-recruit mortality are accounted for. In practice, measurement error and difficulties in establishing robust recruitment -environment relationships complicate the picture. For 5 fish stocks of 4 species in 3 ecosys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 46 publications
1
48
0
Order By: Relevance
“…In other words, recruitment to the local population takes place at a specific time (falling water season, when current velocities are decreasing, and thus, relatively less energy may be needed to swim upstream). Given the discrete size mode for the YOY fishes, it may be feasible to establish a long-term monitoring program focused on applying an annual index of recruitment, which could be useful to determine when harvest rates may be getting excessive and to better understand environmental effects on recruitment (e.g., Stige et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, recruitment to the local population takes place at a specific time (falling water season, when current velocities are decreasing, and thus, relatively less energy may be needed to swim upstream). Given the discrete size mode for the YOY fishes, it may be feasible to establish a long-term monitoring program focused on applying an annual index of recruitment, which could be useful to determine when harvest rates may be getting excessive and to better understand environmental effects on recruitment (e.g., Stige et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The situation is further complicated by the temperature−recruitment relation also displaying spatial differences within the same sea . Still, Stige et al (2013) showed that environmental information can aid the prediction of recruitment. Furthermore, while much of the year class strength is determined during egg and larval stages, this pattern may be overshadowed by density-dependent mortality factors operating at later life stages .…”
Section: Discussionmentioning
confidence: 99%
“…They found that abundance indices of later life stages do not always provide better estimates than those based on earlier life stages, and suggest that this unexpected result was due to the poor quality of the time series collected for older life stages. Stige et al (2013) showed that the inclusion of environmental indices often improved the accuracy of 'honest' predictions of recruitment, i.e. predictions based upon data not used when fitting the recruitment models.…”
Section: (3) Predicting Fish Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, compared to simple models based on juvenile abundance only, environmental correlates may contribute signifi cantly in explaining fi sh recruitment variation (Stige et al 2013). Also, larger ocean basin-scale factors refl ective of climate, such as the El Niño Southern Oscillation (ENSO) and the Pacifi c Decadal Oscillation (PDO) multivariate indexes, may also aff ect salmon production (Beamish and Bouillon 1993;Hare and Francis 1995;Mantua et al 1997;Francis et al 1998;Hare et al 1999).…”
Section: Introductionmentioning
confidence: 99%